Apathetic encephalopathy in thyreotoxicosis: an unsual cause of wernicke encephalopathy and osmotic demyelinating syndrome: An unsual cause of wernicke encephalopathy and osmotic demyelinating syndrome - Mutti, Carlotta; Ciliento, Rosario; Parrino, Liborio; Florindo, Irene; Pavesi, Giovanni; Zinno, Lucia (Acta Biomedica Atenei Parmensis, 2021)
Non-alcoholic Wernicke Encephalopathy (WE) is an overlooked complication of malnourishment in all its forms including undernutrition, inadequate vitamine intake and endocrinological diseases. Both delay in treatment and overtreatment can lead to severe neurological life-long consequences. Inadequate management in patients with chronic malnutrition may cause abrupt osmolytes unbalance and subsequent osmotic demyelination syndromes.  We describe a 65-year old man with apathetic encephalopathy caused by thyreotoxicosis and associated with malnutrition and severe thiamine depletion.